The relationship of Depression Anxiety and Stress Scale and Harmon Jones with Noise in Isfahan Steel Industry Workers - hadi alimoradi; Ruhollah FALLAH MADAVARI; Mahsa NAZARI NAZARI; Reza JAFARINODOSHAN; Mohammad Javad ZARESAKHVIDI; Alireza AJDANI (Shahid Sadoughi University of Medical Sciences, 2021)
Introduction: Loud noise is one of the harmful factors that affects industry workers seriously. In the steel industry, a wide range of equipment and machinery are used in the production processes, which are considered as the sources of annoying noise. Sound has immediate and delayed harmful effects on the process of concentration and increases blood pressure. The aim of this study was to investigate the effect of noise in two different ranges in the control and case groups within the authorized (between 60 to 85 dB) and unauthorized (above 85 dB) categories in the steel industry. Methods: This cross-sectional study was conducted among 300 workers in Isfahan Steel Industries. Environmental sound assessment was performed to determine the distribution of sound pressure level according to the ISO 9612 standard in the company's production units. In this method, the number of exposed people, the exposure time, and the weight factor corresponding to the sound pressure level were calculated in 30 minutes. The DASS-42 and Harmon Jones (DARQ) questionnaires were used to predict the mental state of the participants and to measure the severity of mood swings and arousal. The collected data were analyzed using SPSS statistical software (ver22). Results: Based on the findings, age had a significant effect on depression, marital status had a significant effect on anxiety, and work shift had a significant effect on the level of stress and cognitive dissonance of employees. The stress mean was significantly higher in the case group (14.40 ± 1.66) than the control group (p <0.001). This indicates the effect of sound intensity level on the increase of stress and cognitive dissonance of workers in a noisy environment. With increasing exposure to sound, the participants' stress decreased (p <0.05). Conclusion: Considering the positive and significant relationship of noise level with stress and cognitive inconsistency of workers in the case group, it is necessary to take effective preventive measures to prevent psychological harm and maintain the workers' health in this industry. In order to reduce noise, a number of applicable solutions have been proposed including spatial planning, selection of suitable materials, control of noise pollution related to outdoor construction, control of noise pollution related to indoor construction, and training.